Pilkada - Redaksi, Redaksi (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2008)
This article presents the result of the study about direct local government election process in several districts in Indonesia. Local government elections, known as Pilkada, have conducted since mid-2005, there are hundreds of regions (provinces, districts and municipalities) have conducted Pilkada, and hundreds move will do the same in the years ahead.